Pemberdayaan Masyarakat Melalui Pelatihan Basic Cargo Bagi SMKA Lampung dan SMKN 4 Depok - Wynd Rizaldy; Mustika Sari; Reni Dian Octaviani (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
The background of this training comes from the necessity to provide Aviation students in the transportation and logistics field with knowledge concerning Basic Cargo in the aviation industry. The purpose of this Community empowerment service is to enrich the students' knowledge, preparing them for future employment in the airline industry, and certifying them with Basic Cargo knowledge in compliance with applicable regulations. This service activity was conducted from June 12 to 14, 2022, for SMK Aviation Branti Lampung and SMKN 4 Depok. The method used for implementing this service involved conducting training through relaxed but focused conversations using online media, specifically Zoom, with the students. The results of this service indicated that the students' understanding improved from 44% to 90%, as shown in the pre and post-tests conducted among 30 participants from SMK Lampung and Depok. The understanding level increased by an average of 46%.